ANALISIS TINGKAT PENCEMARAN GAS CO, NO2, DAN SO2 PADA DAERAH BATU MERAH KOTA AMBON - Yusthinus Thobias Male (LPPM, Institut Teknologi Sepuluh Nopember, 2021)
Batu Merah Village is one of the villages in Ambon City which has the largest population and also the main route of transportation access to Ambon City so that the traffic density triggers smoke pollution. This research was conducted to determine the concentration of gas CO, NO2 and SO2 on Batu Merah Village. The results of this study indicate that the level of NO2 and SO2 gas is still below the quality standard, while the CO gas pollution level has exceeded the quality standard based on the Regulation of the State Minister of the Environment No. 12 of 2010.